Blurring boundaries: work-life balance and unbounded work in academia. The role of flexibility, organisational support and gender. (3rd April 2022) - Johnston, Karen; Tanwar, Jagriti; Pasamar, Susana; Van Laar, Darren; Bamber Jones, Annali
ABSTRACT: The paper explores whether work-life balance (WLB) is affected by the unbounded work context and how organisational support, work flexibility and gender affect this relationship. It is a quantitative study, involving a survey of academics based in three UK institutions, using OLS regressions. There is a significant negative relationship between the perception of the unbounded nature of work and WLB among academics, irrespective of their gender. While flexible work and organisational support are positively associated with WLB, they have limited effect in an unbounded work context. This study makes original contributions for practitioners and academics. First, it provides empirical evidence of the relationship between the unboundedness of work and WLB, and finds no significant gender differences in WLB within an unbounded work context. Second, it helps to understand how flexible work and an organisational support culture are insufficient to eliminate the negative effect of unbounded work. Although the research involves a relatively small sample of UK academics provides insights into WLB in an unbounded work context. As became evident during the coronavirus pandemic, the boundaries between work and non-work domains in contemporary work settings are more and more blurred. Work will therefore become increasingly unbounded, potentially undermining WLB and causing tension between growing work demands and the necessities of family and personal lives.